Lifespan models of athlete development: What have we learned from previous attempts? - Baker, Joseph; Gayman, Amy; Johnston, Kathryn (Frontiers in Sports and Active Living, 2023)
Sport has a unique place in many cultures, emphasizing the links between physical elements of movement with psychological and social outcomes. Sport participation continues to attract the interest of researchers from a range of perspectives, yet there remains a strong need to understand the “who”, “what”, “where”, “when” and “why” aspects of sport involvement over the life course. While the research literature includes multiple athlete development models that consider these components, they are incomplete frameworks for understanding lifespan sport engagement. In this article, we discuss the value in building multidimensional developmental models of sport participation that encapsulate experiences across all ages and stages of competitive and recreational sport, and pay special attention to the high degree of complexity of the movement between and within sport both competitively and recreationally. In addition, we highlight several challenges to creating such a lifespan development model, and consider areas of future direction to overcome some of these hurdles.